LESBIAN MARGINALIZATION CONSTRUCTION IN SURABAYA PAGI DAILY NEWSPAPER - Afdholy, Nadya; Andalas, Eggy Fajar; Irawan, Dody; Rochmaniyah, Arif Fatchur (Anaphora : Journal of Language, Literary, and Cultural Studies, 2020)
Power not only operates through formal channels, law, and state institutions but also operates through a series of discourse to define something or a group as incorrect or bad. This study aims to describe the process of paralleling the construction of the Surabaya Pagi newspaper by using a critical analysis of Theo Van Leeuwen's model. This study uses a descriptive qualitative method to see the formation of an opinion on a newspaper text entitled "Narkoba Jaringan Lesbian: Dua Cewek Lesbian Bratang Gede di Pasok Bandar Dinoyo". The data in this study are news excerpts related to exclusion and inclusion. The data source in this study is the Surabaya Pagi newspaper. Data collection techniques in this research are by reading, understanding, and marking relevant quotations in the newspaper text. Data analysis techniques in this research are by identifying, classifying, analyzing, interpreting, and concluding. The results of this study indicate that lesbians are an easy target to build a bad image in the eyes of the public by forming a discourse that excludes the role of drug dealers (who are actually perpetrators of crime) and explores the role of users (lesbians) with a portion of the coverage that further builds the community's image of the group lesbians as a group that is truly wrong and a source of social problems increasingly corner the group's position in society.